Comparative Evaluation of Ketoconazole 400 mg Single Dose Versus Ketoconazole 200 mg Daily for Five Days in Pityriasis Versicolor - Jha, Harendra Kumar; Dhali, Tapan Kumar; Amatya, Ritu (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Many treatments have been attempted in pityriasis versicolor with different reports of success. No direct comparative study between Ketoconazole 400 mg single dose against Ketoconazole 200 mg od for 5 days have been made earlier. The aim of this study was to study and compare the therapeutic efficacy of oral ketoconazole 400 mg single dose with oral ketoconazole 200 mg once daily for 5 days in pityriasis versicolor. Methods: This was a randomized controlled trial. Patients were randomized to receive either ketoconazole 400 mg single dose (group A) or ketoconazole 200 mg daily for 5 days (group B). Altogether 80 patients were taken, 40 in each group. Patients were assessed after 8 weeks and both clinical and mycological evaluation was done. The treatment success (mycological cure) was defined by a negative KOH at 8 weeks post treatment. Chi-square test was used to identify the significance of the variables. Results: The mycological cure at 8 weeks was 46% in group A and 74% in group B and the result was significant. No significant adverse event was noted in any of the groups. Conclusions: There was significant difference in the treatment outcome in both the groups. Ketoconazole 200 mg daily for 5 days had superior efficacy than ketoconazole 400 mg single dose. There was no significant difference in the adverse events. Key words: Ketoconazole, Pityriasis versicolor